Loss of Rice Yields Due to Rice Ragged Stunt Virus (RRSV) on Several Varieties (Inpari 32, Inpari 42, Inpari 16, and Ciherang) in Madiun - Yeni Trias Kurniawati; Wahyu Niken Febrianti; Christina Ika Novidiarsih; Guntur Jumantoro; Khoirul Mukhtar (Nusantara Science and Technology Proceedings, 2022)
Rice Ragged Stunt Virus (RRSV) is one of the plant diseases or annoyances in rice plants where the Brown Planthopper (Nilaparvata lugens Stal) is the vector. In the first dry season (MK 1) in 2022, the area of rice plants in Madiun experienced symptoms of RRSV almost reaching 10%. Most farmers grow the Inpari 32 rice variety which has various advantages, including grain weight, high yield percentage and the brightly colored character of the grain. But in first dry season (MK 1) of 2022, Inpari 32 is a rice variety that is heavily attacked by RRSV. This study was carried out on 4 varieties, each Inpari 32, Inpari 42, Inpari 16, and Ciherang, with the aim of knowing whether there were noticeable differences in the intensity of RRSV attacks and yield losses in the four varieties. Data collection was carried out in 19 villages in Madiun. The results of the 5% Tukey HSD Test found a noticeable difference, Inpari 42 is the variety that shows the least yield loss among 3 other varieties, each Inpari 32, Inpari 16, and Ciherang.